The Sign Language interpreter in the education field: problems and proposals for improvement - Uría Fernández, Marina; Ferreira Villa, Camino (Revista Complutense de Educación, 2016)
The Sign Language interpreter is a learning resource for students with hearing disability that contributes to the development of a bilingual experience in Spanish educational centers. This study focuses on the Sign Language interpreter as an essential part of the learning environment of deaf students in the Autonomous Community of Castile and Leon. The general aim of this study is to analyze the obstacles that block and facilitate the work of the Sign Language interpreter in schools of Castile and Leon. To that end, we carried out a qualitative methodology using descriptive and evaluative exploratory techniques and the SWOT analysis for interpreting the results. The research sample consisted of ten Sign Language interpreters working in state schools of Castile and Leon during the 2013/2014 academic year. They were selected through the qualitative technique of key informants. The results highlight the lack of awareness that the educational community has about the role of the Sign Language interpreter, the lack of normative criteria that equitably regulate the participation of this professional at the center, and finally, the Need for a greater integration of this professional in the education field in order to improve the quality of the bilingual experience of deaf students. Some of the most relevant proposals that could be used in order to overcome the weaknesses and enhance strengths that were identified in this study, are to promote teamwork among all educational and social agents, to increase awareness and counseling of the entire educational community and the development of individualized strategies adapted to the needs of each of the students.